Emotional, intellectual, and communicative characteristics of myopic patients with different levels of anxiety/depression - Drozdov , Volodymyr (The Ukrainian Scientific Medical Youth Journal, 2025)
myopia has been traditionally viewed as a consequence of the interplay between genetic, ethnic, and environmental risk factors. This disease affects people’s psychological development. The aim – is to assess the peculiarities of emotional, intellectual, and communicative character traits of the person left with myopia in various manifestations of anxiety and depression. 200 patients with moderate myopia and mild myopic astigmatism in both eyes were examined. The «Kettel Test» was used to study the characteristics of the patient’s character, and the Hospital Anxiety and Depression Scale was used to identify the levels of depression and anxiety. Methods of mathematical statistics were used for mathematical processing of the research results. The main characteristics of communicative features of patients with myopia are outgoing, supportive, somber, prudent, uninhibited, bold, docile, submissive, suspicious, private, shrewd, and self-sufficient. The main intellectual features of people with myopia are imaginative, close-minded, and traditional. The main emotional features of people with myopia are stable, calm, conscientious, apprehensive, organized, precise, stressed, and tough-minded. Patients with myopia and middle-level anxiety/depression were more close-minded, traditional, and tough-minded. Persons with a high level of anxiety/depression were more reserved, detached, somber, prudent, trusting, outgoing, social, and concrete thinkers. Determination of the prevalence of anxiety and depression, characterological features of patients with myopia if they are present, and compliance features of such patients should be the basis of their rehabilitation programs. Determination of emotional, intellectual, and communicative features of patients with myopia should be based on the study of etiopathogenetic factors of the formation of nosogenies of this pathology and the development of conceptual approaches to rehabilitation, improving their quality of life.